Cancel Culture sebagai Sistem Autopoietik: Logika Penghukuman Sosial di Dunia Digital dalam Perspektif Niklas Luhmann - Simarmata, Yohana Vanessa Rebecca; Sitorus, Fitzerald Kennedy (Jurnal Humaniora : Jurnal Ilmu Sosial, Ekonomi dan Hukum, 2025)
The cancel culture phenomenon is increasingly prevalent in the contemporary digital landscape, marked by the practice of social punishment against individuals or groups who are considered to have violated collective norms on social media. This study aims to analyze cancel culture as an autopoietic system through the perspective of Niklas Luhmann, focusing on its operationally closed characteristics and its ability to reproduce its own communication structure. The study uses a qualitative approach based on literature studies, with data sources in the form of scientific articles, books, and documentation of cancel culture cases on digital platforms. The results of the study show that cancel culture forms an independent communication system, which processes external input based on its own internal logic. In conclusion, cancel culture as an autopoietic system explains how social surveillance in the digital era has become more fragmented, emotional, and difficult to control, while challenging assumptions about justice, participation and reconciliation in public communication spaces in the digital world.